Database design for weather station and power sources - Lim, Shen Yeong. (2013)
Fossil fuel has been used as the main source of energy to power most of the human activities for the past century. It has depleted the resource and brings substantial harm to the environment thus far. This has brought many experts in the world to look into the studies of renewable resources like wind and solar energy which are readily available as long as the sun continues to rise.